2022
DOI: 10.1038/s41467-022-34758-9
|View full text |Cite
|
Sign up to set email alerts
|

Absolute frequency metrology of buffer-gas-cooled molecular spectra at 1 kHz accuracy level

Abstract: By reducing both the internal and translational temperature of any species down to a few kelvins, the buffer-gas-cooling (BGC) technique has the potential to dramatically improve the quality of ro-vibrational molecular spectra, thus offering unique opportunities for transition frequency measurements with unprecedented accuracy. However, the difficulty in integrating metrological-grade spectroscopic tools into bulky cryogenic equipment has hitherto prevented from approaching the kHz level even in the best cases… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Then, in order to minimize the detrimental effects of the vibrations from the PT on the HFC components, we act on two fronts [17].…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…Then, in order to minimize the detrimental effects of the vibrations from the PT on the HFC components, we act on two fronts [17].…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…Slow beam velocities in the laboratory frame and a wide applicable temperature range are important characteristics of buffer gas cooling. Currently, numerous spectroscopic studies using buffer gas cooling have been reported. …”
Section: Introductionmentioning
confidence: 99%
“…Using saturation effects to cancel the Doppler widths and shifts, we can resolve them and determine the transition frequency with an uncertainty of 10 MHz, which is three times smaller than that of the previous study. There have been some reports on Doppler-free spectroscopy of molecules cooled by a buffer gas. ,,, However, these studies have mainly focused on stable molecules or diatomic radicals. This study demonstrates that buffer-gas-cooled Doppler-free spectroscopy is possible for polyatomic radicals with an uncertainty of 10 MHz with a simple extension of a usual absorption measurement setup in the buffer gas cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 A considerable number of transitions have been measured for acetylene isotopologues with close to kHz accuracy. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In this regard, the comprehensive study of ref. 1 concerning the experimental spectroscopic measurements on the parent isotopologue, 12 C 2 H 2 , should be considered incomplete: at the time the MARVEL dataset was assembled, results from several important precision-spectroscopy studies were simply not available and a few existing ones were not utilized to their full extent.…”
Section: Introductionmentioning
confidence: 99%